Qualitative Content Analysis – A Research Method in Social Science - Komor, Marcin; Grzyb, Karolina (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
This paper discusses qualitative content analysis (QCA) as one of the qualitative research methods and its prospective implementation in social research. The article presents the genesis of the content analysis method, with emphasis on the QCA technique. It scrutinises the scope, characteristics, basic principles and techniques of QCA. It also tackles the issue of methodological rigour criteria and quality assurance measures of this research method, aimed at ensuring the credibility of the research. This article also demonstrates the general run of the QCA model proposed by Mayring. Finally, this paper evaluates computer-aided research as part of QCA.